PENGARUH PAJAK WARUNG KOPI (WARKOP) TERHADAP PENDAPATAN ASLI DAERAH DI KOTA GORONTALO - Ramlah Alkatiri; Wahyudin Wange (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
This research was conducted at the Gorontalo City Financial Agency. The purpose of this study was to analyze the effect of coffee shop tax (Warkop) on Regional Original Revenue (PAD). This study uses a quantitative approach, with and analytical tools are simple linear regression and simple correlation. The data source used is the secondary time series data from 2012-2017.The results of the analysis carried out showed that the tax on coffee shops in Gorontalo City gave a positive effect even though it was not significant to the increase in Regional Original Tax revenues. Not significant effect of coffee shop tax receipts, can be seen from the RSquare value = 0.327 or 32.7%. The amount of contribution can be seen from the results of a simple regression equation that is formed, namely; Ŷ = 56,597.42 + 181,927X. Keywords: Influence, Taxes, Coffee Shops, Local Revenue